The Prognostic value of CRP, PCT, and TNF-α, D-lactate, DAO, and endotoxin on Survival of Patients with Severe Craniocerebral Injury: Prognostic value of CRP, PCT, and TNF-α, D-lactate, DAO, and endotoxin - Gong, Ming; Peng, Han (Journal of Medical Biochemistry, 2025)
Background: Hyperbaric oxygen therapy is an important treatment method for early consciousness recovery and rehabilitation after brain trauma. In this study, we investigated the effects of hyperbaric oxygen combined with probiotics nutritional supplements (PNS) on patients with severe craniocerebral injury complicated with swallowing disorders in Intensive care unit. Methods: 74 patients with severe craniocerebral injury who received hyperbaric oxygen therapy in the ICU of our hospital from July 2020 to October 2023 were selected for retrospective analysis. Among them, 35 patients received conventional NS (control groups), and and another 39 patients received PNS (research group). Inflammatory factors, T-lymphocyte subsets, and gastrointestinal mucosal function were compared between the two groups before and after treatment. In addition, patients’ neurological function was assessed using the Glasgow Coma Scale (GCS), Fugl-Meyer Assessment (FMA), and the National Institutes of Health Stroke Scale (NIHSS). Finally, the incidence of adverse effects between the two groups was counted. Results: Compared with the control group, the research group had lower NIHSS and inflammatory factors after treatment, while FMA and GCS were higher (P<0.05). In addition, the immune function and gastrointestinal mucosal function were better in the study group (P<0.05). However, there was no statistically significant difference in the safety comparison between the two groups (P>0.05) . Conclusion: Hyperbaric oxygen combined with PNS can better improve neurological function in patients with severe craniocerebral injury and is recommended for clinical use.